Development of School Administration Skills for Phrapariyattidhamma School Administrators, General Education Section - แก้วพิลา, พระวรธนกร กิตฺติญาโณ; บุญปู่, สมศักดิ์; เรืองสังข์, ระวิง; จันทร์เรือง, สมหมาย (Journal of Educational Review Faculty of Education in MCU, 2018)
This research aims to study the current state of school administration skills, to develop school administration skills, and to propose development process of school administration skills for Phrapariyattidhamma school administrators, general education section. The mixed research methods were used in the study. The data were collected by questionnaires from 556 samples for factor analysis and from 201 samples for check list, and then analyzed by percentage, mean, and standard deviation. The qualitative data were collected from in-depth interviews with 10 experts and group discussions with 10 experts, and analyzed by content analysis. The research results found that: 1. In the current situation of administration in Phrapariyattidhamma schools, the administration is unsystematic, school development cannot cope with the social changes, decision authority depends on the hierarchy system, and the administrative structure is not clear and lacks of good governance. 2. The possibility in development of school administration skills for Phrapariyattidhamma school administrators, general education section was at the high level overall. The accuracy was at the highest level, followed by usefulness and appropriateness respectively. 3. The development process of school administration skills for Phrapariyattidhamma school administrators, general education section consists of 5 main parts; 1) 5 skill components of school administrators, 2) 5 development processes in school administration skills, 3) 5 types of development in school administration skills, 4) 6 components of school administration, and 5) 5 activities in skill development. Furthermore, Papanika Dhamma; vision, capable of administrating and human relation, is also necessary to administrators of Phrapariyattidhamma schools, general education.